Design and Implementation of COTS-Based Aircraft Data Network Using Embedded Linux - Wijiutomo, Catur Wirawan; Ariyanto, Endro (Universitas Muhammadiyah Malang, 2017)
Aircraft Data Network (ADN) is a data communication developed specifically for the aircraft environment. In such environments required data communication system that can work in real time and has a high level of reliability. One of the standards in ADN is Avionics Full-Duplex Switched Ethernet (AFDX) based on the ARINC 664 specification that is data communication standard for ADN that uses IEEE 802.3 standard on physical layer 1 and 2. It becomes the gap and challenge to implement the standard on the component of COTS By utilizing Linux-based embedded systems. The features designed and implemented in this paper are the switching and fault tolerant data components of ARINC 664. From the tests obtained, several results show that ADN functional features can be implemented and can simulate ADN mechanisms including fault tolerance capabilities. But there are performance limitations that the average jitter value of 3380 microseconds obtained has not met the requirements for use on aircraft that should be in the range of 500 microseconds.